2011
DOI: 10.1007/bf03353660
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Multi-walled Carbon Nanotubes/ZnO Nanocomposites using Absorbent Cotton

Abstract: This letter focuses on the synthesis of multi-walled carbon nanotubes (MWNTs) and MWNTs/ZnO nanocomposites using absorbent cotton. The MWNTs have been synthesized by a rapid heating of absorbent cotton at different temperature (400℃, 550℃, 600℃). The MWNTs/ZnO nanocomposites have been synthesized by heating mixtures of Zn(OH)2/H2O/absorbent cotton at different temperature (at about 550℃ and 600℃). The X-ray diffraction (XRD) pattern and energy dispersive spectrum (EDS) clearly show that the pure MWNTs and ZnO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Recently, it has been reported that ZnO can be an alternative to conventional treatments for removing dye pollutants from water [ 3 ]. ZnO, with a lower cost, absorbs over a larger fraction of UV spectrum and absorbs more light quanta than TiO 2 [ 4 ]. When an appropriate light source illuminates ZnO, electron/hole pairs will be produced with electrons absorbing the light energy, transitioning to the conduction band and leaving positive holes in the valence band [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been reported that ZnO can be an alternative to conventional treatments for removing dye pollutants from water [ 3 ]. ZnO, with a lower cost, absorbs over a larger fraction of UV spectrum and absorbs more light quanta than TiO 2 [ 4 ]. When an appropriate light source illuminates ZnO, electron/hole pairs will be produced with electrons absorbing the light energy, transitioning to the conduction band and leaving positive holes in the valence band [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Experience gained from the green synthesis of ENMs has shown that plant leaves can serve as a "factory" for synthesizing various kinds of ENMs such as Ag, Au, ZnO, and CuO ENMs. [59,[77][78][79] A common method to synthesize metallic ENMs is to use reactive phytochemicals in plant leaf extracts (e.g., flavonoids, glucose, and fructose) to reduce the metal salt precursor. [80] It is reasonable to conclude that ENMs may also be reduced by those plant-generated substances.…”
Section: Enms Transformation Inside Plantsmentioning
confidence: 99%
“…A few examples of the synthesis of CNTs from both cellulose and lignocellulosic biomass have been reported, making use of bulk pyrolysis [ 147 ]. For example, absorbent cotton [ 148 ], after treatment at temperatures of 400–600 °C, yielded CNTs with inner and outer diameters of 10 and 80 nm, respectively, after a purification step involving ethanol and water. Cellulose acetate [ 149 ], pyrolyzed in the presence of polyisocyanate and the pre-catalyst NiCl 2 at 750 °C, yielded CNTs with 24–38 nm diameter.…”
Section: Carbon-based Nanostructured Materialsmentioning
confidence: 99%